AIAA/AAS Astrodynamics Specialist Conference and Exhibit 2008
DOI: 10.2514/6.2008-7508
|View full text |Cite
|
Sign up to set email alerts
|

NASA's Planned Return to the Moon: Global Access and Anytime Return Requirement Implications on the Lunar Orbit Insertion Burns

Abstract: Abstract. Lunar orbit insertion LOI is a critical maneuver for any mission going to the Moon. Optimizing the geometry of this maneuver is crucial to the success of the architecture designed to return humans to the Moon. LOI burns necessary to meet current NASA Exploration Constellation architecture requirements for the lunar sortie missions are driven mainly by the requirement for global access and "anytime" return from the lunar surface. This paper begins by describing the Earth-Moon geometry which creates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Long after the Apollo era, Wagner (1994) developed a new launch window strategy for the Lunar Scout Program launched at fixed azimuth by varying the translunar trip time, which is the converse of the strategy employed in Apollo, and compared Atlantic and Pacific TLIs. More recently, NASA's planned return to the Moon (Garn et al, 2008) attempted to protect for a 6 hour TLI window for Earth departure, and found that the frequency of TLI opportunities is dependent on the geocentric wedge angle (i.e. relative inclination) between the initial translunar trajectory plane and lunar orbital plane.…”
Section: Introductionmentioning
confidence: 99%
“…Long after the Apollo era, Wagner (1994) developed a new launch window strategy for the Lunar Scout Program launched at fixed azimuth by varying the translunar trip time, which is the converse of the strategy employed in Apollo, and compared Atlantic and Pacific TLIs. More recently, NASA's planned return to the Moon (Garn et al, 2008) attempted to protect for a 6 hour TLI window for Earth departure, and found that the frequency of TLI opportunities is dependent on the geocentric wedge angle (i.e. relative inclination) between the initial translunar trajectory plane and lunar orbital plane.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies (Jesick and Ocampo, 2011a;Garn et al, 2008;Condon, 2007;Jesick and Ocampo, 2011b) have reported on the development of the lunar orbit insertion (LOI) sequence for placing the lunar lander into a desired circular lunar destination orbit (LDO). Such an LDO with specified altitude, inclination and right ascension of the ascending node is mainly a function of the lunar landing site latitude and longitude.…”
Section: Introductionmentioning
confidence: 99%
“…The circular restricted three-body model is adopted to observe the trend in overall LOI velocity impulses for different LDO orientations. The optimization of the three-burn orbit insertion sequences from the translunar trajectory is studied by Garn et al (2008). The overall LOI velocity impulse performances for covering the entire lunar globe are optimized and mapped onto the contour plots.…”
Section: Introductionmentioning
confidence: 99%
“…After the Apollo project, especially when the evidences of water in lunar south-pole are discovered by many lunar polar orbiters [1], new plans for the manned lunar mission by the USA and other countries have become more diverse. The National Aeronautics and Space Administration (NASA) have published three important reports on the Constellation Program after 2005 [2][3][4].…”
Section: Introductionmentioning
confidence: 99%